Specific roles for Group V secretory PLA2 in retinal iron-induced oxidative stress. Implications for age-related macular degeneration - Rodriguez Diez, Guadalupe (2013)
Iron accumulation and oxidative stress are hallmarks of retinas from patients with age-related macular degeneration (AMD). We have previously demonstrated that iron-overloaded retinas are a good in vitro model for the study of retinal degeneration during iron-induced oxidative stress. In this model we have previously characterized the role of cytosolic phospholipase A2 (cPLA2) and calcium-independent isoform (iPLA2). The aim of the present study was to analyze the implications of Group V secretory PLA2 (sPLA2), another member of PLA2 family, in cyclooxygenase (COX)-2 and nuclear factor kappa B (NF-κB) regulation. We found that sPLA2 is localized in cytosolic fraction in an iron concentration-dependent manner. By immunoprecipitation (IP) assays we also demonstrated an increased association between Group V sPLA2 and COX-2 in retinas exposed to iron overload. However, COX-2 activity in IP assays was observed to decrease in spite of the increased protein levels observed. p65 (RelA) NF-κB levels were increased in nuclear fractions from retinas exposed to iron. In the presence of ATK (cPLA2 inhibitor) and YM 26734 (sPLA2 inhibitor), the nuclear localization of both p65 and p50 NF-κB subunits was restored to control levels in retinas exposed to iron-induced oxidative stress. Membrane repair mechanisms were also analyzed by studying the participation of acyltransferases in phospholipid remodeling during retinal oxidation stress. Acidic phospholipids, such as phosphatidylinositol (PI) and phosphatidylserine (PS), were observed to show an inhibited acylation profile in retinas exposed to iron while phosphatidylethanolamine (PE) showed the opposite. The use of PLA2 inhibitors demonstrated that PS is actively deacylated during iron-induced oxidative stress. Results from the present study suggest that Group V sPLA2 has multiple intracellular targets during iron-induced retinal degeneration and that the specific role of sPLA2 could be related to inflammatory responses by its participation in NF-κB and COX-2 regulation.